Oxidative Stress in Cardiovascular Diseases and Obesity: Role of p66Shc and Protein Kinase C. (27th March 2013) - De Marchi, Elena; Baldassari, Federica; Bononi, Angela; Wieckowski, Mariusz R.; Pinton, Paolo
Abstract : Reactive oxygen species (ROS) are a byproduct of the normal metabolism of oxygen and have important roles in cell signalling and homeostasis. An imbalance between ROS production and the cellular antioxidant defence system leads to oxidative stress. Environmental factors and genetic interactions play key roles in oxidative stress mediated pathologies. In this paper, we focus on cardiovascular diseases and obesity, disorders strongly related to each other; in which oxidative stress plays a fundamental role. We provide evidence of the key role played by p 66 Shc protein and protein kinase C (PKC) in these pathologies by their intracellular regulation of redox balance and oxidative stress levels. Additionally, we discuss possible therapeutic strategies aimed at attenuating the oxidative damage in these diseases.